Analisis Pengendalian Persediaan Bahan Baku Kedelai pada Home Industry Tahu Tukiran Artomoro - Yosua Wijaya Wardoyo; Juli Antasari Br Sinaga; Debora Exaudi Sirait (Bulletin of Community Engagement, 2024)
This research aims to determine the inventory control of soybean raw materials applied to the Tahu Tukiran Artomoro Home Industry, to determine the number of orders for economical soybean raw material supplies at the Artomoro Tahu Tukiran Home Industry. The type of research used in this research is descriptive comparative research method. The data processed is in the form of an inventory report on the purchase and use of soybean raw materials at the Tahu Tukiran Artomoro Home Industry in 2023. The data analysis technique used in this research is a tabular approach, and using the Economic Order Quantity (EOQ) method, Reorder Point calculation techniques. (ROP), Safety Stock, Total Inventory Cost. Based on the results of research on the formula approach model using the EOQ method, the economic order quantity for soybean raw materials was obtained, namely 2,335 kg, with an ordering frequency of 14 times, safety stock of 2,715 kg, ROP can be carried out when the soybean raw materials in the warehouse are 123 kg , and total inventory costs of IDR 341,030. The conclusion of this research shows that the application of the Economic Order Quantity (EOQ) method shows a more economical order quantity compared to the method used by the Tahu Tukiran Artomoro Home Industry.